A Completely New and Sudden Reality: English Language Teacher’s Voices on Emergency Remote Teaching in Indonesian Pesantren Schools - Madkur, Ahmad; As’ad, Muhammad Syihab (Anglophile Journal, 2024)
Unexpected shift to emergency remote teaching (ERT) engendered a complex situation for all schools around the globe, in particular those with inadequate prior experience of this distant online learning mode. Whilst the bulk of research has dealt with ERT practices in various school contexts, this issue in Indonesian pesantren – a type of Islamic boarding school which provides full-time comprehensive religious educational activities but have considerably lack of practice in distance online learning – remains underexplored. This qualitative study addressed this gap by unpacking English language teachers’ voices and experiences in ERT in pesantren school contexts. The study was conducted during school closure in 2021 due to the Covid-19 pandemic and its data were generated through open ended questionnaires and analyzed using six-phase thematic analysis. The findings show that the teachers indicated positive attitude toward ERT. Despite several challenges, they expressed opportunities that might potentially contribute to the better enactment of ERT in pesantren learning process. Pedagogical implications and recommendations for further research are discussed. Keywords: Emergency Remote Teaching, ELT, Pesantren School